PUSAT REHABILITASI KANKER PASCA PENGOBATAN PADA WANITA DI BANJARMASIN - Yolanda, Fenni; Hartono, Rudi (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
Cancer is the most feared and deadly malignant disease, death from cancer is not only due to the disease but also due to the after-effects of cancer treatment. The high number of cancer sufferers is not comparable to health facilities that can cope with cancer such as in Banjarmasin. Health facilities in Banjarmasin are still inadequate, not only in terms of the number of facilities but also in the design of the building which does not pay attention to the patient's psychology. For this reason, a Post-Medication Cancer Rehabilitation Center in Women was designed which focuses on tackling patients who experience physical disorders caused by cancer treatment. This building aims to provide a place that can facilitate cancer sufferers in improving their quality of life and enthusiasm for life. The concept used is "Healing" which means healing, aspects of the healing concept are applied through nature, the senses, and psychology into the building. This concept is expected to be a solution to the problem of cancer health facilities in Banjarmasin.